The Effect of Project Management System Implementation, BIM Technology, and Cloud Collaboration on Construction Project Efficiency in Riau - Aris Krisdiyanto; Benelekser Tumanggor; Ade Octaviansyah; Herman Purwoko Putro; Kemmala Dewi (Westscience Press, 2024)
This study examines the impact of Project Management System (PMS) implementation, Building Information Modeling (BIM) technology, and Cloud Collaboration on construction project efficiency in Riau, Indonesia. Utilizing a quantitative research design, data were collected from 190 professionals involved in construction projects and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The findings reveal that all three factors—PMS implementation, BIM technology, and Cloud Collaboration—positively and significantly influence construction project efficiency. Among these, BIM technology demonstrates the strongest impact, followed by Cloud Collaboration and PMS implementation. The high R² value (0.752) indicates that these factors collectively explain a substantial portion of the variance in project efficiency. This study underscores the importance of integrating advanced technological tools and management practices to enhance project outcomes in the construction industry. The results provide practical insights for construction firms in Riau and similar regions, suggesting that the adoption of BIM, Cloud Collaboration, and PMS can lead to significant improvements in project efficiency.